Gardnerella vaginalis in vaginal secretions present in quilombola women in the municipality of Bequimão-MA - Dutra Texeira, William (2023)
The female reproductive system confers the form in which the vagina and cervix are organs that are considered complex and concentrate a considerable amount of aerobic and anaerobic bacteria of the natural vaginal microbiota. Gardnerella vaginalis plays a keys role in the development of bacterial vaginosis since the vagina is a suitable environment for its colonization, including by strictly anaerobic bacteria, which is associated with BV. Characterize the relationship between vaginal secretions and Gardnerella vaginalis infection in quilombola women. This is a descriptive, cross-sectional study, about the population was formed by quilombola women between 15 and 75 years of age. The Data was collected based on the cytopathological examination request form, the interview was conducted and personal information and sociodemographic data were collected. From a total of 140 participants, 25% were positive for Gardnerella vaginalis. With respect to the age bracket between 31-45 years, there was a prevalence of 44.3%, p= 0.8344. Regarding marital status, the largest group was married women or stable unions with 75 members, and only 14 women (18.66%) are associated with Gardnerella vaginalis with p= 0.2843. Concerning the Amsel test, A Whiff's test and Cells test, p <0.0001 was found. The sociodemographic profile of the quilombola women, showed a higher frequency of women between the ages 31 to 45 years, who studied up to primary schools, who were married, non-alcoholic and non-smokers. Gardnerella vaginalis-related inflammation represented 25% of the exams performed.